Preparation method and application of high-performance water-permeable concrete
By improving the preparation method of permeable concrete, using polycarboxylic acid water reducer and citric acid, and preparing modified composite particles and fillers through materials such as nanosilicon dioxide, zirconium oxychloride and modified glass fiber, the traditional permeable water is solved. The problem of insufficient concrete strength and water permeability has achieved the preparation of high-performance water permeability concrete, which is suitable for seasonal drainage of high-performance pavements and rainwater.
Patent Information
- Application Number
- CN202411586907.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-08
AI Technical Summary
Due to the limitations of material composition and preparation process, traditional permeable concrete has poor ease, uneven pore distribution, insufficient strength and freeze-thaw resistance, and is prone to freeze-thaw damage, low water permeability coefficient, limited environmental protection performance, and cannot meet high performance. Seasonal drainage requirements for pavement and rainwater.
High-performance permeable concrete is prepared by stirring coarse aggregate, fine aggregate, filler, retarder and cement, and adding water and water reducing agent to mix during the stirring process. The method includes using polycarboxylic acid water reducer and citric acid as water reducer and retarder, and preparing modified composite particles and fillers through materials such as nanosilicon dioxide, zirconium oxychloride and modified glass fiber to lift concrete water permeability and compressive strength.
It achieves high strength, excellent water permeability and excellent impact wear and corrosion resistance, suitable for widespread promotion and application in high-performance pavement and rainwater seasonal drainage needs.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of permeable concrete and relates to a preparation method of high-performance permeable concrete and application thereof. Background Art
[0002] Pervious concrete is an eco-friendly building material that not only has excellent water permeability and air permeability, but also has efficient water storage capacity and attractive decorative effects. This material is particularly worth promoting in the construction of "sponge cities". Pervious concrete not only meets the performance requirements of road use, but also can coexist harmoniously with the natural environment, effectively improve the thermal balance of the ground, and promote surface water circulation. It is of great importance to increase urban groundwater resources, alleviate the urban heat island effect, and improve the urban climate.
[0003] Pervious concrete is usually composed of cementitious materials, coarse aggregate, water and admixtures. Since it does not contain fine aggregate, a high porosity is formed in the concrete structure, which allows water to penetrate smoothly. However, due to the limitations of its material composition and preparation process, traditional pervious concrete often leads to poor workability, uneven pore distribution, insufficient strength and freeze-thaw resistance, easy to suffer from freeze-thaw damage, low permeability coefficient, limited environmental performance, unable to meet the standards for paving high-performance roads, and unable to meet the needs of seasonal drainage of rainwater, which limits the application and popularization of pervious concrete products. In addition, there are still some problems with the pervious concrete on the market in actual engineering applications, such as insufficient bearing capacity, weak bonding between coarse aggregates, low permeability coefficient, low freeze-thaw resistance and strength, easy to crack and difficult to repair, and clogging of cavities. These factors shorten its service life and further limit the development potential of pervious concrete. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing high-performance permeable concrete and its application. The high-performance permeable concrete provided by the present invention not only has high strength after molding, but also exhibits excellent permeability and outstanding resistance to abrasion and erosion.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A method for preparing high-performance permeable concrete comprises the steps of mixing coarse aggregate, fine aggregate, filler, retarder and cement, and adding water and a water reducing agent to mix the mixture during the mixing process.
[0007] As a preferred technical solution of the present invention, the high-performance permeable concrete includes the following components by weight: 200-240 parts of coarse aggregate, 50-58 parts of fine aggregate, 1-2 parts of water reducer, 20-30 parts of filler, 0.2-0.3 parts of retarder, 90-100 parts of cement and 40-50 parts of water; the water reducer is at least one of polycarboxylic acid water reducer, naphthalene water reducer, aliphatic water reducer, melamine water reducer and aminosulfonate water reducer; the retarder is selected from at least one of citric acid, sodium citrate, carboxyethyl cellulose, gluconic acid, sodium pyrophosphate, salicylic acid and tartaric acid.
[0008] As a preferred technical solution of the present invention, the preparation method of the filler comprises the following steps:
[0009] 1) immersing the nano-silicon dioxide in a sodium hydroxide aqueous solution, slowly adding zirconium oxychloride and stirring, standing, filtering and collecting the solid, washing to neutrality, vacuum drying and calcining to obtain composite particles;
[0010] 2) placing the composite particles in anhydrous ethanol and mixing them evenly, adding the amino compound and stirring and mixing them, adding the aromatic aldehyde and stirring at a constant temperature, centrifuging, washing, and vacuum drying to constant weight to obtain modified composite particles;
[0011] 3) The modified composite particles, modified glass fibers, polypropylene, styrene, glycidyl methacrylate and an initiator are kneaded and melt-extruded to obtain a filler.
[0012] In step 1), the soaking treatment time is 40-50 minutes; the stirring time is 50-60 minutes; the standing time is 1-2 hours; the vacuum drying temperature is 80°C; and the calcination is calcined at 560-600°C for 2-3 hours.
[0013] In step 1), the concentration of the sodium hydroxide aqueous solution is 30wt%; the mass ratio of the nano-silicon dioxide, the sodium hydroxide aqueous solution and the zirconium oxychloride is 10-12:40-50:2.4-3.0.
[0014] As a preferred technical solution of the present invention, in step 2), the stirring and mixing is stirring at a temperature of 30-40°C for 30-40 minutes; the constant temperature stirring is stirring at a speed of 600-700r / min and a temperature of 60-70°C for 5-6 hours; the washing is washing three times with anhydrous ethanol; and the vacuum drying temperature is 80°C.
[0015] As a preferred technical solution of the present invention, in step 2), the mass ratio of the composite particles, anhydrous ethanol, amino compound and aromatic aldehyde is 8-10:40-50:1.2-1.4:1.8-2.3; the amino compound is 2-aminoterephthalic acid; and the aromatic aldehyde is 3-(4-hydroxyphenyl)acrolein.
[0016] As a preferred technical solution of the present invention, in step 3), the temperature of the melt extrusion is 200-220° C.; and the initiator is azobisisobutyronitrile.
[0017] As a preferred technical solution of the present invention, in step 3), the mass ratio of the modified composite particles, modified glass fibers, polypropylene, styrene, glycidyl methacrylate and initiator is 4-5: 0.8-1.2: 7.2-8.0: 0.6-0.8: 1.2-1.6: 0.05-0.06.
[0018] As a preferred technical solution of the present invention, the modified glass fiber is a glass fiber modified by a vinyl silane coupling agent; the vinyl silane coupling agent is KH-570; the modified glass fiber is prepared by mixing anhydrous ethanol, glass fiber and vinyl silane coupling agent in a mass ratio of 1:6:0.2, stirring at 60°C for 4h, filtering and drying.
[0019] The invention discloses application of high-performance permeable concrete prepared by the preparation method in pavement.
[0020] Beneficial effects of the present invention:
[0021] (1) The high-performance permeable concrete provided by the present invention not only has high strength after molding, but also exhibits excellent permeability and outstanding resistance to abrasion and erosion.
[0022] (2) The preparation process of this high-performance permeable concrete is simple and its performance is excellent, making it very suitable for wide promotion and application. DETAILED DESCRIPTION
[0023] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0024] Example 1
[0025] The high-performance permeable concrete comprises the following components by weight: 200 parts of coarse aggregate, 50 parts of fine aggregate, 1 part of water reducer, 20 parts of filler, 0.2 parts of retarder, 90 parts of cement and 40 parts of water; the water reducer is a polycarboxylate water reducer; and the retarder is citric acid.
[0026] The preparation method of the filler comprises the following steps:
[0027] 1) Soaking nano-silicon dioxide in a sodium hydroxide aqueous solution for 40 minutes, slowly adding zirconium oxychloride and stirring for 50 minutes, standing for 1 hour, filtering and collecting solids, washing to neutrality, vacuum drying at 80° C., and calcining at 560° C. for 2 hours to obtain composite particles; the concentration of the sodium hydroxide aqueous solution is 30wt%; the mass ratio of the nano-silicon dioxide, the sodium hydroxide aqueous solution and the zirconium oxychloride is 10:40:2.4;
[0028] 2) After the composite particles are placed in anhydrous ethanol and mixed, an amino compound is added and stirred at 30°C for 30 minutes, an aromatic aldehyde is added and stirred at 60°C for 5 hours at a speed of 600 r / min, centrifuged, washed three times with anhydrous ethanol, and vacuum dried at 80°C to constant weight to obtain modified composite particles; the mass ratio of the composite particles, anhydrous ethanol, amino compound and aromatic aldehyde is 8:40:1.2:1.8; the amino compound is 2-aminoterephthalic acid; the aromatic aldehyde is 3-(4-hydroxyphenyl)acrolein;
[0029] 3) The modified composite particles, modified glass fiber, polypropylene, styrene, glycidyl methacrylate and initiator are mixed and melt-extruded at 200° C. to obtain a filler; the initiator is azobisisobutyronitrile; the mass ratio of the modified composite particles, modified glass fiber, polypropylene, styrene, glycidyl methacrylate and initiator is 4:0.8:7.2:0.6:1.2:0.05.
[0030] The modified glass fiber is prepared by mixing anhydrous ethanol, glass fiber and vinyl silane coupling agent in a mass ratio of 1:6:0.2, stirring at 60°C for 4 hours, filtering and drying; the vinyl silane coupling agent is KH-570.
[0031] A method for preparing high-performance permeable concrete comprises the steps of mixing coarse aggregate, fine aggregate, filler, retarder and cement, and adding water and a water reducing agent to mix the mixture during the mixing process.
[0032] Example 2
[0033] The high-performance permeable concrete includes the following components by weight: 213 parts of coarse aggregate, 53 parts of fine aggregate, 1.3 parts of water reducer, 23 parts of filler, 0.23 parts of retarder, 93 parts of cement and 43 parts of water; the water reducer is a polycarboxylate water reducer; and the retarder is citric acid.
[0034] The preparation method of the filler comprises the following steps:
[0035] 1) Soaking nano-silicon dioxide in a sodium hydroxide aqueous solution for 45 minutes, slowly adding zirconium oxychloride and stirring for 53 minutes, standing for 1.5 hours, filtering and collecting solids, washing to neutrality, vacuum drying at 80° C., and calcining at 570° C. for 2.5 hours to obtain composite particles; the concentration of the sodium hydroxide aqueous solution is 30wt%; the mass ratio of the nano-silicon dioxide, the sodium hydroxide aqueous solution and the zirconium oxychloride is 10.7:43:2.6;
[0036] 2) After the composite particles are placed in anhydrous ethanol and mixed, an amino compound is added and stirred at 33°C for 33 minutes, an aromatic aldehyde is added and stirred at 630 r / min and 63°C for 5.5 hours, centrifuged, washed three times with anhydrous ethanol, and vacuum dried at 80°C to constant weight to obtain modified composite particles; the mass ratio of the composite particles, anhydrous ethanol, amino compound and aromatic aldehyde is 8.7:43:1.3:2; the amino compound is 2-aminoterephthalic acid; the aromatic aldehyde is 3-(4-hydroxyphenyl)acrolein;
[0037] 3) The modified composite particles, modified glass fiber, polypropylene, styrene, glycidyl methacrylate and initiator are mixed and then melt-extruded at 207° C. to obtain a filler; the initiator is azobisisobutyronitrile; the mass ratio of the modified composite particles, modified glass fiber, polypropylene, styrene, glycidyl methacrylate and initiator is 4.3:0.9:7.5:0.67:1.3:0.053.
[0038] The modified glass fiber is prepared by mixing anhydrous ethanol, glass fiber and vinyl silane coupling agent in a mass ratio of 1:6:0.2, stirring at 60°C for 4 hours, filtering and drying; the vinyl silane coupling agent is KH-570.
[0039] A method for preparing high-performance permeable concrete comprises the steps of mixing coarse aggregate, fine aggregate, filler, retarder and cement, and adding water and a water reducing agent to mix the mixture during the mixing process.
[0040] Example 3
[0041] The high-performance permeable concrete includes the following components by weight: 227 parts of coarse aggregate, 55 parts of fine aggregate, 1.7 parts of water reducer, 27 parts of filler, 0.27 parts of retarder, 97 parts of cement and 47 parts of water; the water reducer is a polycarboxylate water reducer; and the retarder is citric acid.
[0042] The preparation method of the filler comprises the following steps:
[0043] 1) Soaking nano-silicon dioxide in a sodium hydroxide aqueous solution for 45 minutes, slowly adding zirconium oxychloride and stirring for 55 minutes, standing for 1.5 hours, filtering out solids, washing to neutrality, vacuum drying at 80° C., and calcining at 580° C. for 2.7 hours to obtain composite particles; the concentration of the sodium hydroxide aqueous solution is 30wt%; the mass ratio of the nano-silicon dioxide, the sodium hydroxide aqueous solution and the zirconium oxychloride is 11.3:47:2.8;
[0044] 2) After the composite particles are placed in anhydrous ethanol and mixed, an amino compound is added and stirred at 37°C for 35 minutes, an aromatic aldehyde is added and stirred at 65°C for 5.5 hours at a speed of 660 r / min, centrifuged, washed three times with anhydrous ethanol, and vacuum dried at 80°C to constant weight to obtain modified composite particles; the mass ratio of the composite particles, anhydrous ethanol, amino compound and aromatic aldehyde is 9.3:47:1.3:2.1; the amino compound is 2-aminoterephthalic acid; the aromatic aldehyde is 3-(4-hydroxyphenyl)acrolein;
[0045] 3) The modified composite particles, modified glass fiber, polypropylene, styrene, glycidyl methacrylate and initiator are mixed and then melt-extruded at 215° C. to obtain a filler; the initiator is azobisisobutyronitrile; the mass ratio of the modified composite particles, modified glass fiber, polypropylene, styrene, glycidyl methacrylate and initiator is 4.7:1.1:7.7:0.73:1.5:0.057.
[0046] The modified glass fiber is prepared by mixing anhydrous ethanol, glass fiber and vinyl silane coupling agent in a mass ratio of 1:6:0.2, stirring at 60°C for 4 hours, filtering and drying; the vinyl silane coupling agent is KH-570.
[0047] A method for preparing high-performance permeable concrete comprises the steps of mixing coarse aggregate, fine aggregate, filler, retarder and cement, and adding water and a water reducing agent to mix the mixture during the mixing process.
[0048] Example 4
[0049] The high-performance permeable concrete comprises the following components by weight: 240 parts of coarse aggregate, 58 parts of fine aggregate, 2 parts of water reducer, 30 parts of filler, 0.3 parts of retarder, 100 parts of cement and 50 parts of water; the water reducer is a polycarboxylate water reducer; and the retarder is citric acid.
[0050] The preparation method of the filler comprises the following steps:
[0051] 1) Soaking nano-silicon dioxide in a sodium hydroxide aqueous solution for 50 minutes, slowly adding zirconium oxychloride and stirring for 60 minutes, standing for 2 hours, filtering and collecting solids, washing to neutrality, vacuum drying at 80° C., and calcining at 600° C. for 3 hours to obtain composite particles; the concentration of the sodium hydroxide aqueous solution is 30wt%; the mass ratio of the nano-silicon dioxide, the sodium hydroxide aqueous solution and the zirconium oxychloride is 12:50:3.0;
[0052] 2) After the composite particles are placed in anhydrous ethanol and mixed, an amino compound is added and stirred at 40°C for 40 minutes, an aromatic aldehyde is added and stirred at 70°C for 6 hours at a speed of 700 r / min, centrifuged, washed three times with anhydrous ethanol, and vacuum dried at 80°C to constant weight to obtain modified composite particles; the mass ratio of the composite particles, anhydrous ethanol, amino compound and aromatic aldehyde is 10:50:1.4:2.3; the amino compound is 2-aminoterephthalic acid; the aromatic aldehyde is 3-(4-hydroxyphenyl)acrolein;
[0053] 3) The modified composite particles, modified glass fiber, polypropylene, styrene, glycidyl methacrylate and initiator are mixed and melt-extruded at 220° C. to obtain a filler; the initiator is azobisisobutyronitrile; the mass ratio of the modified composite particles, modified glass fiber, polypropylene, styrene, glycidyl methacrylate and initiator is 5:1.2:8.0:0.8:1.6:0.06.
[0054] The modified glass fiber is prepared by mixing anhydrous ethanol, glass fiber and vinyl silane coupling agent in a mass ratio of 1:6:0.2, stirring at 60°C for 4 hours, filtering and drying; the vinyl silane coupling agent is KH-570.
[0055] A method for preparing high-performance permeable concrete comprises the steps of mixing coarse aggregate, fine aggregate, filler, retarder and cement, and adding water and a water reducing agent to mix the mixture during the mixing process.
[0056] Comparative Example 1
[0057] Compared with Example 3, Comparative Example 1 is different in that zirconium oxychloride is not used, and the other components, preparation steps and parameters are the same.
[0058] Comparative Example 2
[0059] Compared with Example 3, the difference in Comparative Example 2 is that aniline replaces the amino compound in step 2), and the other components, preparation steps and parameters are the same.
[0060] Comparative Example 3
[0061] Compared with Example 3, Comparative Example 3 is different in that no amino compound is used, and the remaining components, preparation steps and parameters are the same.
[0062] Comparative Example 4
[0063] Compared with Example 3, Comparative Example 4 is different in that p-hydroxybenzaldehyde replaces the aromatic aldehyde in step 2), and the remaining components, preparation steps and parameters are the same.
[0064] Comparative Example 5
[0065] Compared with Example 3, Comparative Example 5 is different in that no aromatic aldehyde is used, and the remaining components, preparation steps and parameters are the same.
[0066] Comparative Example 6
[0067] Compared with Example 3, Comparative Example 6 is different in that the glass fiber is not modified, and the other components, preparation steps and parameters are the same.
[0068] Comparative Example 7
[0069] Compared with Example 3, Comparative Example 7 is different in that glycidyl methacrylate is not used, and the other components, preparation steps and parameters are the same.
[0070] The concretes obtained from Examples 1-4 and Comparative Examples 1-7 were subjected to the following performance tests, respectively. The test results are shown in Table 1.
[0071] Compressive strength test: According to GB / T50081-2002, test the 28d compressive strength of concrete;
[0072] Water permeability test: according to GB / T25993-2010;
[0073] Table 1
[0074] Water permeability coefficient (mm / s) Compressive strength(MPa) Example 1 11.7 48.1 Example 2 12.1 48.8 Example 3 11.5 47.6 Example 4 11.8 48.3 Comparative Example 1 8.7 32.5 Comparative Example 2 9.3 33.8 Comparative Example 3 8.2 30.5 Comparative Example 4 9.5 34.4 Comparative Example 5 8.1 30.2 Comparative Example 6 8.9 32.8 Comparative Example 7 8.3 31.0
[0075] From the test results in Table 1, it can be seen that compared with Comparative Examples 1-7, the concrete prepared in Examples 1-4 of the present invention has excellent water permeability and compressive strength.
[0076] By comparing all the embodiments with the comparative examples, combined with the analysis of Table 1, it can be seen that the present invention has a good connection effect on concrete aggregates through polypropylene, which can promote the improvement of concrete compressive strength and flexural strength; by adding modified composite particles and modified glass fibers to polypropylene materials, the water permeability and compressive strength of concrete can be effectively improved. Specifically, zirconium oxide is generated on the surface of nano-silicon dioxide to form composite particles. Zirconium oxide is a common wear-resistant and high-strength inorganic filler. By compounding it with silicon dioxide, the scale effect of nanoparticles is conducive to improving the compressive strength of permeable concrete, making it not easy to crack. The compounded composite particles also have filtering ability, thereby enhancing the water permeability of permeable concrete.
[0077] The present invention forms a chemical chain bond through 3-(4-hydroxyphenyl) acrolein and 2-aminoterephthalic acid with antioxidant properties, and the molecular chain contains phenolic hydroxyl groups and multiple carboxyl groups, so that the antioxidant property is improved, and free radicals can be effectively captured while forming compounds with higher thermal stability, thereby reducing the damage of free radicals to polypropylene materials under light and heat, thereby ensuring the strength performance of concrete; the composite particles modified by amino compounds and aromatic aldehydes can be uniformly dispersed in the polypropylene material, and the addition of glycidyl methacrylate can react with the active hydroxyl groups and carboxyl groups of the modified composite particles and modified glass fibers, further promoting the compatibility of the modified composite particles and modified glass fibers in the polypropylene material, and the carbon-carbon double bonds contained in the modified composite particles and modified glass fibers can also participate in the copolymerization reaction in the system, so that the binding force of the modified composite particles and the modified glass fibers is improved, and the compressive strength and water permeability of the permeable concrete are enhanced by increasing the dispersibility and binding force.
[0078] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing high-performance permeable concrete, characterized in that: The preparation method comprises the steps of stirring coarse aggregate, fine aggregate, filler, retarder and cement, and adding water and water reducing agent to mix the mixture during stirring to obtain the product; The preparation method of the filler comprises the following steps: 1) immersing the nano-silicon dioxide in a sodium hydroxide aqueous solution, slowly adding zirconium oxychloride and stirring, standing, filtering and collecting the solid, washing to neutrality, vacuum drying and calcining to obtain composite particles; 2) placing the composite particles in anhydrous ethanol and mixing them evenly, adding the amino compound and stirring and mixing them, adding the aromatic aldehyde and stirring at a constant temperature, centrifuging, washing, and vacuum drying to constant weight to obtain modified composite particles; 3) The modified composite particles, modified glass fibers, polypropylene, styrene, glycidyl methacrylate and an initiator are kneaded and melt-extruded to obtain a filler.
2. A method for preparing high-performance permeable concrete according to claim 1, characterized in that: The high-performance permeable concrete comprises the following components by weight: 200-240 parts of coarse aggregate, 50-58 parts of fine aggregate, 1-2 parts of water reducer, 20-30 parts of filler, 0.2-0.3 parts of retarder, 90-100 parts of cement and 40-50 parts of water.
3. A method for preparing high-performance permeable concrete according to claim 1, characterized in that: In step 1), the soaking treatment time is 40-50 minutes; the stirring time is 50-60 minutes; the standing time is 1-2 hours; the vacuum drying temperature is 80°C; and the calcination is calcined at 560-600°C for 2-3 hours.
4. A method for preparing high-performance permeable concrete according to claim 1, characterized in that: In step 1), the concentration of the sodium hydroxide aqueous solution is 30wt%; the mass ratio of the nano-silicon dioxide, the sodium hydroxide aqueous solution and the zirconium oxychloride is 10-12:40-50:2.4-3.
0.
5. The method for preparing high-performance permeable concrete according to claim 1, characterized in that: In step 2), the stirring and mixing is stirring at a temperature of 30-40°C for 30-40 minutes; the constant temperature stirring is stirring at a speed of 600-700r / min and a temperature of 60-70°C for 5-6 hours; the washing is washing three times with anhydrous ethanol; and the vacuum drying temperature is 80°C.
6. A method for preparing high-performance permeable concrete according to claim 1, characterized in that: In step 2), the mass ratio of the composite particles, anhydrous ethanol, amino compound and aromatic aldehyde is 8-10:40-50:1.2-1.4:1.8-2.3; the amino compound is 2-aminoterephthalic acid; and the aromatic aldehyde is 3-(4-hydroxyphenyl)acrolein.
7. A method for preparing high-performance permeable concrete according to claim 1, characterized in that: In step 3), the temperature of the melt extrusion is 200-220° C.; the initiator is azobisisobutyronitrile; the mass ratio of the modified composite particles, modified glass fiber, polypropylene, styrene, glycidyl methacrylate and initiator is 4-5: 0.8-1.2: 7.2-8.0: 0.6-0.8: 1.2-1.6: 0.05-0.
06.
8. The method for preparing high-performance permeable concrete according to claim 1, characterized in that: The modified glass fiber is a glass fiber modified by a vinyl silane coupling agent; the vinyl silane coupling agent is KH-570; the modified glass fiber is prepared by mixing anhydrous ethanol, glass fiber and vinyl silane coupling agent in a mass ratio of 1:6:0.2, stirring at 60°C for 4 hours, filtering and drying.
9. Use of high-performance permeable concrete prepared by the preparation method according to any one of claims 1 to 8 in pavement.
Citation Information
Patent Citations
Preparation method of composite colored stain-resistant coating material for building external wall
CN110724420A
Anti-crack recycled concrete as well as preparation method and application thereof
CN113105180A
High-strength and high-permeable-rate concrete and preparation method thereof
CN115490465A
High ductility, quick-hardening and ultra-early strength type cement concrete composition modified by polymer modifier and the construction method for road pavement using the same
KR102363749B1